The Role and Mechanisms of Antimicrobial Peptides in Overcoming Multidrug-Resistant Bacteria - Jinhui Yang; Junning Zhang; Zeyu Feng; Yunqi Ma (Molecules)
Multidrug-resistant (MDR) bacteria are becoming more and more common, which presents a serious threat to world health and could eventually render many of the antibiotics we currently use useless. The research and development of innovative antimicrobial tactics that can defeat these hardy infections are imperative in light of this predicament. Antimicrobial peptides (AMPs), which have attracted a lot of attention due to their distinct modes of action and capacity to elude conventional resistance mechanisms, are among the most promising of these tactics. As a promising substitute for conventional antibiotics, AMPs are a varied class of naturally occurring compounds that target bacteria membranes and disrupt cellular activities to demonstrate broad-spectrum antimicrobial activity. The objective of this study is to present a thorough summary of the current knowledge regarding AMP mechanisms against MDR bacteria, including immunological modulation, interactions with microbial membranes, and possible synergy with currently used antimicrobial drugs. In addition, we define the review’s scope to include the most recent developments in AMP research, emphasizing the innovations’ development, optimization, and therapeutic promise. We hope to emphasize the crucial role that AMPs will play in the future of antimicrobial therapy by bringing together recent research and highlighting current issues. We also hope to advocate for AMPs’ continued research and development as part of a comprehensive strategy to counteract the growing threat of antibiotic resistance.